The Starling girl [videorecording (DVD)] - Parmet, Laurel; Huron, Lord; Lannin, Brian; Scanlen, Eliza, 1999-; Pullman, Lewis, 1993-; Schmidt, Wrenn; Abrams, Austin, 1996-; Secor, Kyle; Burgum, Jessamine; Green, Claire Elizabeth; Simpson, Jimmi (Decal Releasing, 2023)
Seventeen-year-old Jem Starling struggles with her place within her Christian fundamentalist community. But everything changes when her magnetic youth pastor Owen returns to their church.